Saúde ambiental e migração :uma análise dos impactos da migração venezuelana sobre os serviços hospitalares na cidade Boa Vista-RR - Barreto, Tárcia Millene de Almeida Costa (2021)
Human mobility has accompanied the forrnation of civilizations and the advancement of globalization, being facilitated by the development of technology, means of transport, among others, enabling a greater range of displacements providing the flow of goods, services and symbols. In the state of Roraima since 2014, the reception of Venezuelan migrants has been experienced, which was intensifying at the end of 2016. And this movement has been seen as a problem by the media and local authorities, especially with regard to health issues. From this, the theme of this research arises from the perception of the challenge that is the maintenance of the health of the native and migrant population, due to the vulnerability and reception conditions of Venezuelan migrants in the city of Boa Vista-RR, considering the context of multifactoriality in the triggering of diseases. Therefore, the present research proposes to answer the following questions: Does Venezuelan migration to Boa Vista-RR contribute to the production of health problems related to the environment? To what extent does Venezuelan migration affect public health services, from the perspective of environmental health, in the city of Boa Vista-RR? And had as main objective: To evaluate the impacts on public health, resulting from Venezuelan migration, in the city of Boa Vista-RR, from 2008 to 2018, under the perspective of environmental health. The thesis was organized in four chapters articulated with the specific objectives of the study and, therefore, each chapter had its methodology of analysis. The first had a descriptive qualitative methodology in arder to understand the type of migration of venezuelans to Boa Vista. And the other chapters relied on a descriptive quantitative ethodology, with documentary analysis on secondary data in arder to map the conditions that are conditioned by the environment, from the attendance at the health units; determine the global burden of diseases of the population of Boa Vista-RR (Brazilians and Venezuelans), during the study period; and to compare the computed expenses, by health problem, of the Brazilian and Venezuelan population. Among the results, it was observed that Venezuelan migrants have a mixed-type migratory typology with characteristics of macro and micro sociological and neoclassical theories. That can be classified as migrants for survival. And that they are imposed conditions of social vulnerability that affect the production and social construction of the disease. lt was deterrnined that the main diseases with fractions attributable to the environment that affected the study population were acute respiratory syndromes (SARS), diarrheal diseases, HIV/AIDS, Malaria, neoplasms and malnutrition. Which are diseases that are easily preventable and strongly linked to factors of social inequity, in addition to factors related to health care, such as the low supply of primary care services. Finally, it was identified that as for the financiai increases resulting from the attendance of Venezuelan migrants in public health services in Boa Vista, these represented only 3.60% of the expenses computed in the analyzed historical series. lt is evident that Venezuelan migration did not have negative impacts on the local health system, which only showed problems that already existed.